The VISCACHA survey-deep and resolved photometry of star clusters in the Magellanic Clouds - Dias, Bruno (2019)
The VISCACHA (VIsible Soar photometry of star Clusters in tApii and Coxi HuguA†) Survey is an ongoing project based on deep and spatially resolved photometric observations of Magellanic Cloud star clusters, collected using the SOuthern Astrophysical Research (SOAR) telescope together with the SOAR Adaptive Module Imager. So far we have used >300h of telescope time to observe ∼150 star clusters, mostly with low mass (M < 104MâŠ ) on the outskirts of the LMC and SMC. With this high-quality data set, we homogeneously determine physical properties using deep colour-magnitude diagrams (ages, metallicities, reddening, distances, mass, luminosity and mass functions) and structural parameters (radial density profiles, sizes) for these clusters which are used as a proxy to investigate the interplay between the Magellanic Clouds and their evolution. We present the VISCACHA survey and its initial results, based on our first two papers. The project's long term goals and expected legacy to the community are also addressed.